Synthesis of a dual clickable fullerene platform and construction of a dissymmetric BODIPY-[60]Fullerene-DistyrylBODIPY triad. (5th November 2021) - Rabah, Jad; Yonkeu, Lyne; Wright, Karen; Vallée, Anne; Méallet-Renault, Rachel; Ha-Thi, Minh-Huong; Fatima, Anam; Clavier, Gilles; Fensterbank, Hélène; Allard, Emmanuel
Abstract: The synthesis of a methanofullerene platform bearing on one side an alkyne and on the other a protected alkyne is reported. This clickable fullerene building block was functionalized by two distinct BODIPY azido derivatives using a 1 st CuAAC/alkyne deprotection/2 nd CuAAC, sequence, through either stepwise or one-pot processes in an efficient manner. The triad displays strong absorption from 300 to 700 nm. The strong fluorescence quenching observed for the two BODIPYs within the triad is probably due to photo-induced energy and/or electron transfer events. Graphical abstract: Image 1